2013
DOI: 10.1001/jamaneurol.2013.4598
|View full text |Cite
|
Sign up to set email alerts
|

Mutations inVRK1Associated With Complex Motor and Sensory Axonal Neuropathy Plus Microcephaly

Abstract: IMPORTANCE Patients with rare diseases and complex clinical presentations represent a challenge for clinical diagnostics. Genomic approaches are allowing the identification of novel variants in genes for very rare disorders, enabling a molecular diagnosis. Genomics is also revealing a phenotypic expansion whereby the full spectrum of clinical expression conveyed by mutant alleles at a locus can be better appreciated.OBJECTIVE To elucidate the molecular cause of a complex neuropathy phenotype in 3 patients by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
3
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 20 publications
4
65
3
2
Order By: Relevance
“…We hypothesized a role for VRK1 in neuronal migration based on brain MRIs of affected children ( Fig. 1A-D ;Gonzaga-Jauregui et al, 2013) and the observed effect of the mutation on expression of genes associated with the Reelin pathway. Our results also suggested that VRK1 R358X is a null allele, and furthermore, any residual mutant protein that may be produced will not enter the nucleus .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We hypothesized a role for VRK1 in neuronal migration based on brain MRIs of affected children ( Fig. 1A-D ;Gonzaga-Jauregui et al, 2013) and the observed effect of the mutation on expression of genes associated with the Reelin pathway. Our results also suggested that VRK1 R358X is a null allele, and furthermore, any residual mutant protein that may be produced will not enter the nucleus .…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis showed that the Reelin signaling was the pathway most significantly associated with expression differences in VRK1-mutant cells ( p Ͻ 0.002; Table 1). Reelin signaling is required for proper positioning of neurons within the laminated telencephalon (Rice and Curran, 2001;Frotscher et al, 2009), and also plays a role in neuronal migration in the spinal cord (Yip et al, 2009). The association of altered Reelin pathway expression and the simplified gyral patterns observed in brain MRIs of affected individuals ( Fig.…”
Section: Global Mrna Expression In Vrk1 Homozygous Cells Reveals Altementioning
confidence: 99%
See 2 more Smart Citations
“…29,30 Pathologically, human VRK1 mutations are very rare and are manifested as complex neurodegenerative syndromes in children, in which pontocerebellar hypoplasia, microcephaly, muscular atrophy, and ataxia are components of their clinical phenotype. 31,32 Similarly, many hereditary mutations in DNA repair genes are also clinically manifested as neurodegenerative diseases in children. 33 Gene transcription requires dynamic local remodeling of chromatin.…”
Section: Introductionmentioning
confidence: 99%